Pengaruh Manajemen Pengetahuan Terhadap Kinerja Tenaga Kependidikan: Analisis Model SECI pada Perguruan Tinggi Islam - Fikriana Aribah Al Nashir; Alfi Satria; Sobirin Sobirin (Lembaga Pengembangan Kinerja Dosen, 2025)
Knowledge management (KM) has become a crucial strategy for enhancing organizational effectiveness, including in the higher education sector. Universities require a structured governance of knowledge to support innovation, efficiency, and excellent service to the academic community. Educational staff play a strategic role in the smooth operation of universities, making their ability to manage and share knowledge an essential factor in achieving institutional goals. While previous literature has confirmed a positive relationship between KM and performance, there is a research gap specifically addressing the context of educational staff in Islamic higher education institutions. This study aims to fill that gap by analyzing the influence of KM on the performance of educational staff at the Indonesian Al-Zaytun Islamic Institute (IAI AL-AZIS). This research uses a quantitative approach with a correlational design. The study's population consists of all educational staff members at IAI AL-AZIS as of March 1, 2025, with a census method applied to include the entire population as respondents. Data were collected through a validated and reliable questionnaire, supported by interviews and documentation to strengthen the analysis. Data analysis was performed using simple linear regression, t-test, and the coefficient of determination. The results show that knowledge management has a positive and significant influence on the performance of educational staff at IAI AL-AZIS. The implementation of the knowledge conversion cycle through the SECI model (Socialization, Externalization, Combination, Internalization) was proven effective in improving the quality of administrative services, work efficiency, and staff professionalism. This finding reinforces that effective knowledge management is a strategic factor in human resource development. This study recommends strengthening the culture of knowledge sharing, developing digital repositories, and providing continuous training to support sustainable performance improvement. Further research is suggested to consider additional variables such as work motivation and organizational culture for a more comprehensive understanding.